NEW APPROACHES FOR THE ETIOLOGICAL ASPECTS OF COMMUNITY-ACQUIRED PNEUMONIA IN CHILDREN - Karzhavova , G.A; Davurova , L.Sh; Rakhmonov , R.N (Educational Research in Universal Sciences, 2024)
Pneumonia in children is one of the urgent problems of pediatrics, which is determined by the continuing high level of morbidity and the severity of the prognosis, especially in young children. The results of clinical, radiological, laboratory examination of children with community-acquired pneumonia living in the Samarkand region, its place in the structure of bronchopulmonary pathology in children according to hospitalization data are presented. Shown is the etiological structure of community-acquired pneumonia, the sensitivity of pneumotropic microflora to the main groups of antibiotics. The results obtained underline the age-related characteristics of the course of community-acquired pneumonia in children.